The effect of short-term training on the cardiac structure of Iranian young elite weightlifters - Saleh, V.; Siahkouhian, M.; Anoushiravani-Hamlabad, S.; Eghbal- Moghanlou, A.; Gursoy, R. (International Journal of Applied Exercise Physiology, 2019)
The aim of this study was to evaluate the effect of short-term training on the cardiac structure of Iranian young elite weightlifters. 10 elite male weightlifters from Iran (with an average age of 19.1±3.8 years, weight 104.1±23 kg, height 179.1±4.9 cm) participated in this study as one group. The subjects were tested by one and two-dimensional echocardiography so that their cardiac structure could be determined. From an echocardiographic view, the results showed that there were no significant differences between preparation and competition phases (P>0.05) in terms of the cardiac structure variables. However, athletes' performances showed significant differences in all variables (p < 0.05). It can be concluded that all elite weight lifters were being trained for a long-term- over the years, and all the changes in the echocardiography variables were already made due to the strength of their trainings and a short-term training (from preparation phase to competitive phase) didn`t affect the cardiac structure of the weightlifters. It is suggested that in the future, the researchers may use long term training in order to observe changes in the cardiac structure of weightlifters.